The method of settling environmental conflicts in Indonesia: Alternative dispute resolution - Sari Rafiqa; Darwance Darwance; Anwar Muhammad Syaiful (E3S Web of Conferences)
Rapid progress poses significant dangers to environmental contamination and harm, leading to disruptions in the conservation of the local ecosystem. Damage to the environment and pollution represent a collective responsibility shouldered by society, with the government accountable for all expenses related to restoring the impacted environment. The issues concerning those responsible for environmental harm can be addressed through judicial means or alternative dispute resolution methods. The questions to consider are: First, how is the resolution of environmental conflicts handled outside of court when viewed from a civil law perspective? Second, what challenges exist in resolving disputes outside of the judiciary in Indonesia? The approach taken for this research is normative in nature. The findings indicate that settling disputes outside of court aims to achieve a compensation agreement that mitigates further negative impacts on the environment. Common challenges encountered in out-of-court dispute resolution include differing viewpoints between the party that has suffered harm and the party responsible, as well as the complexities associated with enforcing administrative law that can lead to the withdrawal of business permits, prompting the need to address cases of environmental damage through legal channels.